2020
DOI: 10.1002/ijfe.2303
|View full text |Cite
|
Sign up to set email alerts
|

Credit rating and competition

Abstract: We analyze the effect of competition between credit rating agencies (RA) which trade-off reputation (future income) and rating inflation (current income). We find that relative to monopoly, RA are more likely to inflate ratings under duopoly. Moreover, competition reduces welfare (the net income of the projects that are rated good) if the new entrant has low reputation and increases it if the new entrant has high reputation. Therefore, our results suggest that lowering barriers to entry (thus, allowing low-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…In addition, the paper results also indicate that competition leads to a firm getting a higher initial rating from a CRA than the firm’s existing rating, resulting in rating shopping in the credit rating industry. The findings of the study are consistent with prior literature, which supports that competition among CRAs worsens the quality of credit ratings (Becker et al, 2011; Bolton et al, 2012; Camanho et al, 2022; Flynn & Ghent, 2018; Park & Lee, 2018; Vu et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, the paper results also indicate that competition leads to a firm getting a higher initial rating from a CRA than the firm’s existing rating, resulting in rating shopping in the credit rating industry. The findings of the study are consistent with prior literature, which supports that competition among CRAs worsens the quality of credit ratings (Becker et al, 2011; Bolton et al, 2012; Camanho et al, 2022; Flynn & Ghent, 2018; Park & Lee, 2018; Vu et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Bolton et al (2012) used a model to analyze the impact of competition on credit rating and found that competition reduces efficiency, increases rating shopping, and could result in rating inflation. Camanho et al (2022) used a theoretical model to analyze competition among CRAs and found that competition exacerbates the problem of rating inflation in the credit rating industry. Lee and Schantl (2019) used a model to analyze how the dynamics between competition among CRAs and their gatekeeper’s role impact rating inflation in the industry.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… Bhandari and Golden (2021) found that CRAs had a stronger response to CEO’s political ideology. Camanho et al (2020) revealed that CRAs tended to upgrade credit ratings when facing fierce competition in the credit rating market. However, there is little literature available for how CRAs or credit ratings react to financial news on the internet.…”
Section: Literaturementioning
confidence: 99%